Impact of professional learning on teachers' representational strategies and students' cognitive engagement with molecular genetics concepts. Issue 1 (2nd January 2018) - Nichols, Kim
Abstract: A variety of practices and specialised representational systems are required to understand, communicate and construct molecular genetics knowledge. This study describes teachers' use of multimodal representations of molecular genetics concepts and how their strategies and choice of resources were interpreted, understood and used by students to demonstrate their conceptual understanding. Recordings of teachers' and students' discourse around representations, teacher interviews and student pre- and post-tests were used as data sources. Vignettes of students' dialogue with teachers around the form and function of representations and teacher interview responses highlight higher order conceptual understanding. Coding for cognitive domains within lesson phases where different modes of representation were utilised showed classrooms operated at higher domains compared to lessons where modalities were absent. This study shows how pedagogy that focuses on representational form and function as well as students' engagement in critical discussion around affordances and constraints of representations results in a higher cognitive engagement with molecular genetics knowledge.